Answer:
c=2
Explanation:
hope it helps :)
Simplifying
3 + -1(2c + -8) = 7
Reorder the terms:
3 + -1(-8 + 2c) = 7
3 + (-8 * -1 + 2c * -1) = 7
3 + (8 + -2c) = 7
Combine like terms: 3 + 8 = 11
11 + -2c = 7
Solving
11 + -2c = 7
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '-11' to each side of the equation.
11 + -11 + -2c = 7 + -11
Combine like terms: 11 + -11 = 0
0 + -2c = 7 + -11
-2c = 7 + -11
Combine like terms: 7 + -11 = -4
-2c = -4
Divide each side by '-2'.
c = 2
Simplifying
c = 2